‘New urbanity’ and contemporary forms of public art. Notes on Citizen Firefighter (K. Hunter) - Lossau, Julia (ERDKUNDE, 2008)
In the course of global economic restructuring, ‘new urbanity’ has become a key concept within German-speaking urban studies. Despite a certain ambiguity, the concept often conveys a positive image of the traditional European city and its supposed urban qualities. The present paper aims to challenge this image by drawing upon contemporary forms of public art. Taking Kenny Hunter’s sculpture Citizen Firefighter as a case study, alternative concepts of urbanity are explored. Using qualitative interviews with the artist, the relationship between artistic and academic imaginations of urban life will be discussed. In this way a more balanced image of the traditional European city can be achieved.